(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Oyster mushroom plays a vital role in human nutrition as it supplies the necessary growth factors such as protein, minerals, vitamins in the body. Fresh samples of Oyster mushroom (Pleurotus ostreatus) were collected from the agricultural research farm of Ibrahim Badamasi Babagida. University Lapai, Niger State, Nigeria located at latitude 9.0674oN, longitude 6.5698o E. The aim of this study is to determine the nutritional value of Oyster Mushroom cultivated on some plant substrates. Sawdust, Maize (Zea mays) husk Rice (Oryza sativa) straw and Banana (Musa acuminata) leaves were collected from the Botanical garden of the Department of Biological Sciences, Ibrahim Badamasi Babagida. University Lapai, Niger State. Tissue culture techniques, spawn production, preparation and pasteurization of the plant substrates, inoculation of the mushroom spawn were conducted on the mushroom, nutritional analysis of the cultivated mushroom were determined and conducted using standard methods. The results indicated that among the selected substrates used, mushroom cultivated on banana leaves was found to be high in ash and moisture contents with 7.00% and 16.00 % respectively, rice straw was found the to be high in carbohydrate content with 51.70%. Maize husk was found to be high in crude fat and protein contents with 28.60% and 7.31% respectively, crude fibre content of 7.69% was found to be high in sawdust when compared with the other selected substrates .The present work demonstrated almost all the substrates used have certain levels of nutritive values. Mushroom cultivation under different plant substrates which serve as a bio-remedy of plant waste...